2015
DOI: 10.1016/j.cmi.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and species distribution of candidaemia in Asia: a laboratory-based surveillance study

Abstract: The epidemiology of candidaemia varies between hospitals and geographic regions. Although there are many studies from Asia, a large-scale cross-sectional study across Asia has not been performed. We conducted a 12-month, laboratory-based surveillance of candidaemia at 25 hospitals from China, Hong Kong, India, Singapore, Taiwan and Thailand. The incidence and species distribution of candidaemia were determined. There were 1601 episodes of candidaemia among 1.2 million discharges. The overall incidence was 1.22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
101
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 28 publications
13
101
2
3
Order By: Relevance
“…It appears that the species distribution in our institution is changing. Previous local studies reported a predominance of C. tropicalis , a finding commonly observed in tropical regions [10, 20]. We observed an increasing proportion of C. glabrata from 11% in 2008 to 31% in 2015, overtaking C. tropicalis as the predominant species.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…It appears that the species distribution in our institution is changing. Previous local studies reported a predominance of C. tropicalis , a finding commonly observed in tropical regions [10, 20]. We observed an increasing proportion of C. glabrata from 11% in 2008 to 31% in 2015, overtaking C. tropicalis as the predominant species.…”
Section: Discussionsupporting
confidence: 68%
“…This concurs with the general trend of stability in incidence reported in other developed countries, such as the United States and Europe [2, 17]. A recent study comparing candidemias among sites in Asia indicated that rates in Singapore (0.15 episodes per 1000 patient-days) were comparable with most other Asian countries, with the exception of Taiwan (0.37 per 1000 patient-days) and India (1.24 per 1000 patient-days) [10]. On a more global scale, our rates were lower than those in Italy (0.33 per 1000 patient-days) [18], and Brazil (0.37 per 1000 patient-days) [19].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…3 Representative studies are listed in Table 1. [4][5][6][7][8][9][10][11][12][13][14] The reasons for these differences in candidemia incidence are likely multifactorial, including underlying ecology of Candida spp, differences in underlying patient populations, resources available for medical care and training programs, difficulties in implementing hospital infection control programs, and differences in surveillance methodologies. 3 Although a plethora of single-institution studies have been reported, only a few countries have conducted geographically widespread surveillance, and in still fewer countries has this been sustained over time to describe trends in candidemia.…”
Section: Yeasts Candidamentioning
confidence: 98%
“…The incidence of candidemia varies from 24 to 32.3 episodes/per 10,000 admissions 1, 3, 4 , and the mortality rate was 22–60% 26 . Recent strategies of antifungal prophylaxis or preemptive therapy for selected high-risk patients account for emergence of fluconazole resistant strains and an increased prevalence of non- albicans Candida species 79 .…”
Section: Introductionmentioning
confidence: 99%